Staging an Experience of Cultural Heritage Preservation: Consumers' Willingness to Pay for Heirloom Rice in the Philippines - Britwum, Kofi; Demont, Matty (Wiley, 2025)
The Cordillera Administrative Region in the Philippines is home to terraced rice embedded in centuries of cultural heritage. However, weak market incentives threaten sustained production, jeopardizing indigenous communities' cultural heritage and the in situ biodiversity of rice genetic resources. Demand-side policy interventions have been proposed to address these challenges. Drawing on the experience economy, we staged an experience with urban consumers, offering them the opportunity to participate in cultural heritage preservation through purchasing heirloom rice. Participants first self-selected into white or brown rice market segments as a benchmark. Subsequently, each market segment was invited to (i) identify their preference between their benchmark and heirloom rice, and (ii) bid to upgrade their non-preferred to their preferred rice through a Becker-DeGroot-Marschak (BDM) mechanism. The sample was randomly split between a control group and two "experience treatment" groups exposed to gain- or loss-framed narratives about rice terrace preservation. Results reveal that a subset of consumers in each market segment switched to heirloom rice. White rice consumers were more reluctant to transition to heirloom rice, although they responded positively to the gain-framed narrative, paying the highest price premiums for heirloom rice (PhP 92.55 or US $2.03 per kilogram). Brown rice consumers were more willing to switch but willing to pay lower premiums for heirloom rice, altogether suggesting the need for a segmented marketing strategy. Highlighting nutritional benefits and quality is crucial, but positioning heirloom rice within a gastronomic system that showcases its use in specific dishes and occasions is equally important for enhancing consumer appeal.